Generational Differences in Workforce and Their Effects on Organizational Performance in Canada - Hamid, Dr.Shahnaz (IJRDO-Journal of Applied Science, 2015)
The paper provides the results of the descriptive research on the generational differences in the workforce of Canada. The aspects of the work with Millennials and its effects on the organizational performance were studied with the focus on the data provided by Statistics Canada and other agencies. It was found that the number of Millennials, or representatives of Generation Y, in the Canadian labor force is high, and this fact influences the human resource managers’ practices to improve the organizational performance. The main positive feature of working with Millennials is their orientation to innovations and changes. However, Millennials’ focus on flexible working conditions, high compensation level, and opportunities for the personal and career development influence the turnover rates and the organizational performance accordingly